Fabrication of 3D SiOx structures using patterned PMMA sacrificial layer. (9th January 2018) - Li, Zhiqin; Xiang, Quan; Zheng, Mengjie; Bi, Kaixi; Chen, Yiqin; Chen, Keqiu; Duan, Huigao
Abstract: Three-dimensional (3D) nanofabrication based on electron-beam lithography (EBL) has drawn wide attention for various applications with its high patterning resolution and design flexibility. In this work, we present a bilayer EBL process to obtain 3D freestanding SiO x structures via the release of the bottom sacrificial layer. This new kind of bilayer process enables us to define various 3D freestanding SiO x structures with high resolution and low edge roughness. As a proof of concept for applications, metal-coated freestanding SiO x microplates with an underlying air gap were fabricated to form asymmetric Fabry–Perot resonators, which can be utilized for colorimetric refractive index sensing and thus also have application potential for biochemical detection, anti-counterfeiting and smart active nano-optical devices.